Food safety what you don't know can hurt you (Lawrenceville, N.J. : Meridian Education Corporation, 1996)
Look out at the best ways to prepare, store and maintain food so that it is at its best and healthiest.
Executive producer, Twila Sears.
Keywords: Food handling -- Safety measures; Food contamination; Food poisoning -- Prevention